Prenatal Maternal Psychological Distress and Offspring Risk for Recurrent Respiratory Infections - Laura S. Korhonen; Linnea Karlsson; Noora M. Scheinin; Riikka Korja; Mimmi Tolvanen; Jussi Mertsola; Ville Peltola; Hasse Karlsson (Elsevier, 2022)
Objective
To assess the relation between maternal prenatal psychological distress, comprising depression and anxiety symptoms and relationship quality, and the risk of recurrent respiratory infections (RRIs) in children up to 2 years of age. Children with RRIs frequently use health care services and antibiotics. Prenatal maternal psychological distress can be one, previously unidentified risk factor for RRIs.
Study design
The study population was drawn from a population-based pregnancy cohort in Finland (www.finnbrain.fi). Children with RRIs (n = 204) and a comparison group (n = 1014) were identified by maternal reports at the child age of 12 or 24 months. The Edinburgh Postnatal Depression Scale, Symptom Checklist-90 anxiety subscale, the Pregnancy-Related Anxiety Questionnaire–Revised 2, and the Revised Dyadic Adjustment Scale were used to assess maternal symptoms and parental relationship quality at 34 weeks of gestation. Adjustment for maternal postnatal depressive and anxiety symptoms was performed.
Results
Maternal prenatal Edinburgh Postnatal Depression Scale (OR, 1.24; 95% CI, 1.08-1.44), Symptom Checklist-90/Anxiety (OR, 1.40; 95% CI, 1.01-1.76), Pregnancy-Related Anxiety Questionnaire–Revised 2 (OR, 1.28; 95% CI, 1.11-1.47), and Revised Dyadic Adjustment Scale (OR, 1.32; 95% CI, 1.01-1.58) total sum scores were associated with child RRIs by the age of 24 months. Greater number of siblings, shorter duration of breastfeeding, and the level of maternal education were also identified as risk factors for child RRIs.
Conclusions
Maternal prenatal psychological distress is linked with a higher risk for child RRIs.